People tracking in video - Siah, Wee Kiat. (2012)
It is very easy for humans to track a moving object or people in a video clip and to further analyze it to obtain meaningful information. However, it is difficult to get a computer to perform what humans can do. Furthermore, before computer can do analysis to human behaviours, it must track the human in the first place.